Caracterización edafológica del sector Cumbijín, cantón Salcedo, provincia de Cotopaxi, para la elaboración de la plataforma integrada de datos de la gestión agropecuaria 2018. - Briceño Mena, Norma Rocío (2018)
The edaphological characterization of Cumbijin which belongs to Salcedo is a research Project allowing to understand soil physical and chemical characteristics. This knowledge is the base for agricultural production and the success of future projects. This work will contribute to develop an integrated data platform for agricultural management. The database will require additional agricultural, socio-economic, weather, and edaphological data to optimize technicians’ and farmers’ initiatives based on the edaphological characteristics of the área. We used Geographic Information Systems to extract information and characterize the soils in Cumbijin. We built a weighted table considering the main crops in the area, and based on optimal soil requirements and then suggest the most optimal crops depending on whether this are going to be located in the low, medium or high altitude of Cumbijin. The main Cumbijin’s soil characteristics are: an slope ranging from 12-25% in the center of the region, and an steeper slope (>40%) in the high altitude of Cumbijin. The predominant soil texture is loam and silty loam soil, with a good drainage. The soils are deep (>100 cm) with a pH mildly acid (5.6-6.5) at lower altitudes of Cumbijin and neutral (6.6-7.4). Additionally, there is no presence of saline soils, they contain high amount of organic matter and there is a médium leve lof fertility.